The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/10615806.2017.1384466
|View full text |Cite
|
Sign up to set email alerts
|

Are perfectionism dimensions risk factors for anxiety symptoms? A meta-analysis of 11 longitudinal studies

Abstract: Research is needed to understand the conditions under which the connection between perfectionism and anxiety becomes stronger (e.g., stress).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 58 publications
3
57
0
5
Order By: Relevance
“…To rectify these issues, other‐oriented perfectionism has come to be referred as “other forms of perfectionism” because of the scarce theoretical and empirical work associated with it (Enns & Cox, ; Smith et al, ; Stoeber & Otto, ), whereas parental expectations and parental criticism were referred as “correlates of perfectionism” because they are viewed as childhood antecedents of perfectionism (Sherry & Hall, ; Smith et al, ).…”
Section: Perfectionism: Conceptualization and Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…To rectify these issues, other‐oriented perfectionism has come to be referred as “other forms of perfectionism” because of the scarce theoretical and empirical work associated with it (Enns & Cox, ; Smith et al, ; Stoeber & Otto, ), whereas parental expectations and parental criticism were referred as “correlates of perfectionism” because they are viewed as childhood antecedents of perfectionism (Sherry & Hall, ; Smith et al, ).…”
Section: Perfectionism: Conceptualization and Measurementmentioning
confidence: 99%
“…Related to these behaviors, perfectionists also tend to exhibit self‐defeating behaviors including premature withdrawal of efforts, lack of persistence, procrastination, and disengagement from decisions and actions (Slade & Owens, ; Smith et al, ; Tziner & Tanami, ). For example, Brand and Altstötter‐Gleich () and Frost et al () found that perfectionists with high concern over mistakes avoid tasks or situations that provoke performance evaluations.…”
Section: The Influence Of Perfectionism On Emotions Cognition Behavmentioning
confidence: 99%
See 1 more Smart Citation
“…In their meta-analysis, Smith, Vidovic, Sherry, Stewart, and Saklofske (2017) suggested investigating the link between perfectionism and anxiety. Even though it can't be generalized, within the context of this case this connection -together with the unrelenting standards schema -was observed as demanding parent mode triggering anxiety through perfectionist expectations.…”
Section: Discussionmentioning
confidence: 99%
“…This provides support that even though this literature may initially appear disconnected, it is actually quite cohesive; our definition of personal standards and self-critical perfectionism can be understood within the literature as a whole. Additionally, in a recent meta-analysis the socially-defined measure of perfectionism was not found to be a consistent predictor of outcomes across samples, where as personal standards and self-critical perfectionism were (Smith, Vidovic, Sherry, Stewart & Saklofske, 2018). This provides additional evidence that multidimensional perfectionism as defined by the facets, personal standards and self-critical perfectionism, may be more consistent and generalizable.…”
Section: Perfectionismmentioning
confidence: 91%